2015
DOI: 10.1093/femspd/ftv106
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of non-typeableHaemophilus Influenzaein the pharynx of children with adenotonsillar hypertrophy after treatment with azithromycin

Abstract: This study was performed in children with adenotonsillar hypertrophy to evaluate the effect of azithromycin (AZT) on the presence of NTHi in monocyte/macrophages (CD14(+) cells) of adenoids/tonsils and the persistence of NTHi after adenotonsillectomy. A total of 36 pediatric patients participated in the study: 20 children were treated with AZT before adenotonsillectomy, and 16 children did not receive the antibiotic prior to surgery. NTHi were identified by culture and PCR in swabs and tissue samples. NTHi was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Rapid advances in sequencing technologies now allow for simultaneous profiling of host-pathogen interactions, giving novel insights into the cellular cross-talk occurring during clinically relevant infections. NTHi is still considered an extracellular pathogen, despite increasing evidence of an intracellular lifestyle ( Craig et al, 2001 ; Morey et al, 2011 ; Olszewska-Sosińska et al, 2016 ). NTHi was first demonstrated to be residing and replicating within the phagocytic compartment of mononuclear cells ( Farley et al, 1986 ), but in epithelial cells, NTHi colocalised with acidic compartments displaying late endosomal features and did not appear to be replicating ( Morey et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid advances in sequencing technologies now allow for simultaneous profiling of host-pathogen interactions, giving novel insights into the cellular cross-talk occurring during clinically relevant infections. NTHi is still considered an extracellular pathogen, despite increasing evidence of an intracellular lifestyle ( Craig et al, 2001 ; Morey et al, 2011 ; Olszewska-Sosińska et al, 2016 ). NTHi was first demonstrated to be residing and replicating within the phagocytic compartment of mononuclear cells ( Farley et al, 1986 ), but in epithelial cells, NTHi colocalised with acidic compartments displaying late endosomal features and did not appear to be replicating ( Morey et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this reduction was associated with increased carriage of antibiotic resistance genes by certain bacteria. Furthermore, Olszewska-Sosińska et al, found that persistent NTHi isolates recovered from macrophages obtained from azithromycin-treated children were not azithromycin resistant ( Olszewska-Sosińska et al, 2016 ). As such, rather than active resistance to antibiotics conferred by specific antibiotic resistance genes, the maintenance of persister cells and drug tolerance may occur by other mechanisms, such as downregulation of ribosomes during intracellular persistence.…”
Section: Discussionmentioning
confidence: 99%
“…NTHi colonization in tonsils is less studied, but a significant presence of NTHi in tonsil specimens after tonsillectomy has previously been reported by us and others ( 38 , 62 ). Intracellular survival of NTHi within the tonsillar core has also been linked with resistance to antibiotic treatment, potentially promoting recurrent infection or chronic colonization ( 63 ). Further studies of the similarities between NTHi isolates from the tonsils and LRT are warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Numerous in vitro studies have demonstrated the ability of NTHi to invade and persist within macrophages 32 , 33 , 34 , 35 with in vivo evidence of NTHi intracellular invasion within macrophage‐like cells from adenoid tissue also apparent. 36 , 37 Despite this, the ability of NTHi to persist within macrophages in the asthmatic airway is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although NTHi was previously regarded as an extracellular pathogen, accumulating evidence suggests that NTHi can invade and persist within host immune cells to facilitate airway survival 31 . Numerous in vitro studies have demonstrated the ability of NTHi to invade and persist within macrophages 32–35 with in vivo evidence of NTHi intracellular invasion within macrophage‐like cells from adenoid tissue also apparent 36,37 . Despite this, the ability of NTHi to persist within macrophages in the asthmatic airway is less clear.…”
Section: Introductionmentioning
confidence: 99%